Abschied von den Boomern - Bude, Heinz 1954- (Hanser, 2024)
What remains of the boomers? A portrait of a generation and its contradictions Boomers are leaving the spotlight. Those born between 1955 and 1970 - the baby boomers - have retired or are gradually joining the ranks of the elderly. Boomers are united by the feeling that there were far too many of them, which was evident first in overcrowded classrooms and, later, in the competitive job market. As a result, their basic attitude tends to be sceptical. During a crucial phase of their lives, the experience of AIDS and Chernobyl taught them that nothing can ever be taken for granted. Heinz Bude, an early boomer, describes how his generation is saying goodbye to a lifestyle that shaped society for decades.
Literaturverzeichnis S. 135-[143]
Keywords: Geschichte 1955-1970; Geschichte 1955-2000; Geburtenstarker Jahrgang; Deutschland; 20. Jahrhundert; Bildungsreform; Kalter Krieg; Ökologie; Sozialismus; Tschernobyl; Utopie